2004
DOI: 10.1080/0260293032000158171
|View full text |Cite
|
Sign up to set email alerts
|

Gender, student perceptions, institutional commitments and academic dishonesty: who reports in academic dishonesty cases?

Abstract: The academic dishonesty literature generally focuses on the causes of academic dishonesty, and outlines deterrence strategies, as well as the punishment methods used in formal sanction. Student self-monitoring techniques are becoming a more visible alternative that places greater emphasis on proactive prevention methods as opposed to reactive punishment policies. Increasing the formal level of student responsibility in deterring academic dishonesty assumes that students will actively monitor the behavior of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 27 publications
3
55
2
9
Order By: Relevance
“…The findings also contradict Taylor Bianco and Deeter Schmelz (2007), and Mirshekary and Lawrence (2009) who found that female students were more likely to plagiarise. Consistent with Hendershott, Drinan and Cross (1999), McCabe & Treviño (1997), Rocha and Teixeira (2005a, b), Simon et al (2004) Straw (2002 and Yang's (2014) findings, the act of plagiarising appears to be more prevalent among the males than females in this study. A further cross examination of the act of plagiarism by gender and programme, however, found that a significant difference was found only among the NTP female students.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The findings also contradict Taylor Bianco and Deeter Schmelz (2007), and Mirshekary and Lawrence (2009) who found that female students were more likely to plagiarise. Consistent with Hendershott, Drinan and Cross (1999), McCabe & Treviño (1997), Rocha and Teixeira (2005a, b), Simon et al (2004) Straw (2002 and Yang's (2014) findings, the act of plagiarising appears to be more prevalent among the males than females in this study. A further cross examination of the act of plagiarism by gender and programme, however, found that a significant difference was found only among the NTP female students.…”
Section: Discussionsupporting
confidence: 81%
“…consistently less involved in the act of plagiarism than to male students (Hendershott, Drinan, & Cross, 1999;McCabe & Treviño, 1997;Rocha & Teixeira, 2005a;Straw, 2002;Simon et al, 2004;Ward & Beck, 2001;Yang, 2014), other studies found that female students were more likely to plagiarise (Taylor Bianco & Deeter Schmelz, 2007;Mirshekary and Lawrence (2009). Roig and Caso (2005) and Bilic-Zulle, et al (2005), on the other hand, found that plagiarism rate is not significantly affected by gender.…”
mentioning
confidence: 95%
“…The majority of students who had completed the online module on academic integrity were first-year students, and this could account, at least to some degree, for their conservatism in more contentious cases. This contradicts the findings of several other studies 15,17,36 that suggest older students typically have a more conservative attitude towards cheating.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies have found that "mature" students are less likely to recognize acts of academic misconduct and report cheating compared with younger students. 4,15,17,28 A Scottish cross-sectional study, however, tested students' ability to "recognize foul academic behaviors" and found that most first-year students considered numerous acts of plagiarism reasonable, perhaps because of lack of experience in dealing with such situations. 29 Other researchers have characterized students' justifications for cheating, which first required recognition of these behaviors, and then focused on "neutralization" and excuses, and recognition of the "shades of grey" in condemned behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation